Bulk metallic glasses - Suryanarayana, C.; Inoue, Akihisa (Boca Raton, FL : CRC Press, 2011)
'This book is suitable for young researchers in materials science and applied physics, who are interested in learning about bulk metallic glasses and are looking for a guidebook to launch research into this exciting materials field. Also, this book can be perfectly used as a textbook for students in graduate schools'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Metallic glasses; Bulk solids